MOVE-III: A CubeSat for the detection of sub-millimetre space debris and meteoroids in Low Earth Orbit - Oikonomidou, Xanthi; Karagiannis, Eleftherios; Still, Dominik; Strasser, Florian; Firmbach, Felix S.; Hettwer, Jonathan; Schweinfurth, Allan G.; Pucknus, Paul; Menekay, Deniz; You, Tianyi; Vovk, Maximilian; Weber, Selina; et al. (Frontiers in Space Technologies, 2022)
The Munich Orbital Verification Experiment (MOVE) is a CubeSat student project housed at the Scientific Workgroup for Rocketry and Spaceflight at the Technical University of Munich. MOVE-III is the fourth CubeSat under development, and the first 6U mission of the MOVE project that will carry a dedicated scientific payload in orbit. The mission aims at acquiring in-situ observations of sub-millimetre space debris and meteoroids in Low Earth Orbit, with the objective of compiling a dataset of flux, as well as object mass and velocity measurements that can be used for the validation of the small object estimates of space debris models and support further studies related to the characterisation of the space environment. The MOVE-III CubeSat employs the MOVE-BEYOND platform and is planned to carry three DEDRA plasma ionization sensors. The Preliminary Design Review has been completed in early 2022, with the next milestone being the Critical Design Review, planned for 2023. The paper elaborates on the scientific objectives of the mission and the expected data products, provides an overview of the detector operation principle and presents the overall system architecture, the platform configuration and the subsystem interaction. Considerations on the debris mitigation aspects of the mission are additionally discussed.